Arquitetura da informação pervasiva: contribuições conceituais - Oliveira, Henry Poncio Cruz de [UNESP] (2014)
In the information field, the modern-day impacts are related to the advances of the technique and technology, with the diversity of digital information environments and with the need to deal with informational stocks that not always are transformed into knowledge in the subject's cognitive structure. We found the emergence of new theoretical and practical actions in the Information Architecture subject, whose concern is fixed in the information pervasiveness in physical, digital or hybrid environments. These actions have used the subjects' behavior in daily life as a guide for the production of transparent or ubiquitous technological artifacts. We showed that the Pervasive Information Architecture needs to be better designed in conceptual and theoretical level. We were guided by the following research question: What is the Pervasive Information Architecture and how can it be conceptually represented to deal with current technological demands. We draw as general objective: Build a concept of Pervasive Information Architecture based on phenomenology and Information Science. We start from the thesis that on Pervasive Information Architecture a conceptualization with phenomenological basis and in the perspective of Information Science can be made. We use the quadrupole method and construct the theoretical pole, the epistemological pole, the technical pole and the morphological pole, including phenomenological and systemic perspectives, treated as epistemic foundations of research and framed in the epistemological pole. We conclude theoretically presenting Pervasive Information Architecture in the form of concept, conceptual map and visual representation of the concept, as a way to provide plural mechanisms for concept dissemination to students, researchers, information architects and the like, that may have distinct cognitive preferences for knowledge absorption.